2022
DOI: 10.20289/zfdergi.1037526
|View full text |Cite
|
Sign up to set email alerts
|

Cortical cells, xylem vessels, and chlorophyll biosynthesis improved by acetylsalicylic acid and sodium nitroprusside in peach leaves

Abstract: Objective: Water and nutrients are required for plant growth and development. Transport of water and nutrients from the roots to the shoots occurs in the xylem vessel. Acetylsalicylic acid (ASA) and sodium nitroprusside (SNP) play important roles in plant growth regulation. However, limited information is known about the relationship between SNP and ASA and leaf anatomy. Therefore, the current study was performed to evaluate the hypothesis that ASA and SNP improve leaf cortex and xylem anatomy and chlorophyll … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The NO triggers xylem formation through programmed cell death (Yu et al, 2014). Some studies showed that NO is involved in xylem formation in buds and xylem improvement in leaves (Aras, 2022b;2022c). In the current study we examined xylem conduit diameter of leaf midrib.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The NO triggers xylem formation through programmed cell death (Yu et al, 2014). Some studies showed that NO is involved in xylem formation in buds and xylem improvement in leaves (Aras, 2022b;2022c). In the current study we examined xylem conduit diameter of leaf midrib.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have been conducted in many plant species to determine the effectiveness of SNP under salt stress (Khoshbakht et al, 2018;Shams et al, 2019;Jabeen et al, 2021). Moreover, SNP provided early xylem formation in peach bud (Aras, 2022c) and xylem improvement (Aras, 2022b).…”
Section: Introductionmentioning
confidence: 99%